ADAPTIVE FUZZY SLIDING MODE CONTROL FOR THE TURNTABLE SERVO SYSTEM - HUANG Pei; WANG XinYuan (Jixie qiangdu)
The traditional servo system has the advantages of simple structure and reliability,but it is easy to change with the parameters of the motor,so the anti load disturbance performance is poor,and the robustness is weak. In order to solve this problem,an adaptive fuzzy sliding mode controller is added to the system. As a kind of non continuity control,the biggest advantage is that the sliding mode is completely adaptive to the interference of the system. The integral sliding mode surface is used to design the switching function and the fuzzy method is used to realize the high precision control of linear systems and nonlinear systems. The simulation results show that the adaptive fuzzy sliding mode control is not only robust and fast response speed,but also can greatly weaken the chattering phenomenon of sliding mode control under the similar control effect.